Expérience de la durée : Biennale de Lyon 2005 - Raspail, Thierry; Bourriaud, Nicolas; Chapoulie, Jean-Marc; Jullien, François; Maffesoli, Michel; Obrist, Hans-Ulrich; Sans, Jérôme; Weill, Alain; Biennale Lyon 2005 (Paris : Musées, 2005)
Ackermann, Franz ; Afif, Saadane ; Allora & Calzadilla ; Attia, Kader ; Balducci, Fabio ; Barré, Virginie ; Bock, John ; Bronson, AA ; Buren, Daniel ; Calle, Sophie ; Chan, Paul ; Conrad, Tony ; Creed, Martin ; Crumb, Robert ; Dawson, Verne ; Delvoye, Wim ; Dietman, Erik ; Eliasson, Olafur ; Eno, Brian ; Gastaldon, Vidya ; Geers, Kendell ; General Idea ; Hakansson, Henrik ; Höller, Carsten ; Huebler, Douglas ; Huyghe, Pierre ; Janssens, Ann Veronica ; Kusolwong Surasi ; Lambie, Jim ; Lin, Michael ; Malaval, Robert ; Marioni, Tom ; Matta-Clark, Gordon ; Meckseper, Josephine ; Mekas, Jonas ; Miller, John ; Mréjen, Valérie ; Muller, Dave ; Neuenschwander, Rivane ; Nguyen-Hatsushiba, Jun ; Ohanian, Melik ; Ono, Yoko ; Parreno, Philippe ; Peinado, Bruno ; Riley, Terry ; Roth, Dieter ; Ruppersberg, Allen ; Sierra, Santiago ; Taaffe, Philip ; Tayou, Pascale Marthine ; Thurnauer, Agnès ; Tiravanija, Rirkrit ; Tremblay, John ; Tunick, Spencer ; Turrell, James ; Uklanski, Piotr ; Verschaere, Fabien ; Wang Du ; Warhol, Andy ; Wurm, Erwin ; Young, La Monte
Exhibition. Biennale de Lyon 2005. BAC (Biennale d'Art Contemporain) Lyon. 2005-09-14. 2005-12-31
biog., geselect. ind. tent. & gr. tent. p. 312-347
boek
Keywords: Lyon